Film Appreciation among the People of Jaffna: A Study Based on Cinema Theatres - Raguram, S.; Thevayasi, V. (Department of Tamil, University of Jaffna, 2020)
Cinema theatres are considered important centers to enjoy cinemas. It is widely assumed that the complete technical depth of a cinema can only be fully enjoyed in a theatre that plays an important role in providing relaxation and creating awareness among the public. This research looks into the initiation of theatres in the Jaffna region, their growth, the ways in which they exist for a longer period of time, and the factors responsible for the growth of cinema taste based on theatres. To understand the kinds of lifestyles, relaxations and awareness provided by theatres to the general public, data and information were gathered from multiple sources: theatre owners, managers, employees, film reviewers, commentators and audiences through interviews and focus group discussions. The thorough analysis of data confirmed that the film appreciation transformed as an individual taste from a taste of group, theatres lost their prominence through the proliferation of television, and also watching movies in theatres and succeeding debates and discussions are on the brink of extinction.
Keywords: Theatres; Film Appreciation; Entertainment; Pacification